The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1682/jrrd.2007.10.0158
|View full text |Cite
|
Sign up to set email alerts
|

Content validity of a home-based person-environment interaction assessment tool for visually impaired adults

Abstract: Abstract-Home-based assessments require in-depth analyses of daily living difficulties. No assessment tool that has been validated with visually impaired adult subjects has allowed such analysis. This research adapted a home-based personenvironment interaction assessment tool designed for persons who are visually impaired. The Model of Competence, an explanatory model of the person-environment relationship, served as the conceptual framework. A qualitative study was conducted with professionals, visually impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Carignan et al (2008) reported that performance and environment are intertwined and cannot be understood separately. Current research lacks thorough verbal descriptions of the occupational performance experiences of persons with low vision in their daily environment.…”
Section: Introductionmentioning
confidence: 99%
“…Carignan et al (2008) reported that performance and environment are intertwined and cannot be understood separately. Current research lacks thorough verbal descriptions of the occupational performance experiences of persons with low vision in their daily environment.…”
Section: Introductionmentioning
confidence: 99%
“…Although several home safety assessments are available, none are designed to evaluate specific issues related to sensory features, including environmental visibility and how the person interacts with his or her personal space. Carignan, Rousseau, Gresset, and Couturier (2008), a research team that developed a French version of a home assessment for people with low vision, emphasized that the issue is not whether people with vision loss can prepare a meal but whether they can prepare the meal in their home with specific environmental support such as lighting, contrast, and organization.…”
mentioning
confidence: 99%
“…[23] These tools are specific in addressing one or two components such as light and the use of colour and contrast or the use of technical devices. The items of the EOVI are partially based on the EVOLVE tool of Lewis and Torrington, [24] a checklist for extra care-housing for people with sight loss, and the homebased assessment tool validated by Carignan, Rousseau, and Couturier.…”
Section: Discussionmentioning
confidence: 99%
“…The items of the EOVI are partially based on the EVOLVE tool of Lewis and Torrington, [24] a checklist for extra care-housing for people with sight loss, and the homebased assessment tool validated by Carignan, Rousseau, and Couturier. [23] In the EOVI-63, "Furnishing & Obstacles" is added as an extra aspect because of the risk of falling. [25] The experts in this study considered these items to be relevant.…”
Section: Discussionmentioning
confidence: 99%